Regional gastrointestinal transit times in severe ulcerative colitis - Haase, A. M.; Gregersen, T.; Christensen, L. A.; Agnholt, J.; Dahlerup, J. F.; Schlageter, V.; Krogh, K. (Neurogastroenterology and motility, 2016)
Background Gastrointestinal (GI) dysmotility may present secondary to inflammatory bowel disease. The main aim of this study was to investigate GI motility in ulcerative colitis (UC) patients during severe disease activity. Methods Twenty patients with severe UC were studied with a novel telemetric capsule system (3D‐Transit) designed for minimally invasive, ambulatory assessment of total and regional GI transit times. Ten patients were available for follow‐up during remission. Data were compared to those of 20 healthy subjects (HS). Key Results Total GI transit time was significantly longer in patients with severe UC (median 44.5 h [range 9.9–102.7 h]) than in HS (median 27.6 h [range 9.6–56.4 h]) (p = 0.032). Additionally, during severe UC, transit time was prolonged through the proximal colon (p = 0.003) and there were strong trends toward longer than normal small intestinal transit time (HS: median 4.9 h [range 3.4–8.3 h] vs severe UC patients: median 5.9 h [range 3.9–11.9 h]; p = 0.053) and colorectal transit times (HS: median 18.2 h [range 1.5–43.7] vs severe UC patients: median 34.9 h [range 0.4–90.9 h]; p = 0.056). Our data further indicate that total GI and colorectal transit times may be prolonged in UC during early remission. Conclusions & Inferences Total GI transit times are significantly prolonged during severe UC. Using a novel telemetric capsule system, 3D‐Transit, total and regional gastrointestinal motility and transit patterns were described in patients with ulcerative colitis during severe disease. Total gastrointestinal transit time is prolonged during severe ulcerative colitis. Furthermore, passage through the proximal part of the colon is prolonged during severe inflammation.